Effects of the ECB's communication on government bond spreads - Sebastian Camarero Garcia; Frederik Neugebauer; Jan Russnak; Lilli Zimmermann (Deutsche Bundesbank, 2023)
This paper investigates the financial market effects of the ECB's communication on the Pandemic Emergency Purchase Programme (PEPP). Using data for 10 euro area countries, we first analyse the impact of different communication channels such as press releases, ECB blog contributions, speeches and interviews on changes in government bond spreads. Second, we assess whether spreads react differently to communication by specific ECB Executive Board members. Markets turn out to be sensitive to both the communication channel and the communicating ECB Executive Board member.
Keywords: E52; E58; G14; 330; Event study; central bank communication; ECB; PEPP; sovereign yields